HUBUNGAN ANTARA POLA PENANAMAN NILAI TERHADAP TINGKAT KEPATUHAN KARYAWAN INDOMARET DI KECAMATAN TAMPAN KOTA PEKANBARU - Hendra Purnama; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Research purpose of this is to know what are the values Indomaret applied by the company and the factors that influence employees Indomaret to comply with the values that have been applied by the company Indomaret. Research using quantitative methods by using data retrieval in Indomaret in the District Handsome. To determine the number of employees in Indomaret in the District Handsome and to know clearly the number of respondents in the field use the method with simple random sampling technique to assign respondents involved in this research. Field data into numbered population sample of 121 employees, it is set at 67,7% of the total population of 82 employees (respondents). To collect data from respondents used direct observation methods, interviews and documentation, to the processing of data in use quantitative methods. This research is to see human beings always have a variety of needs. Respondents who joined as an employee Indomaret generally have middle and upper income, and rarely encountered troubled employees with salary because it has an adequate income. As creatures who are never satisfied, they have a variety of ways to meet their needs with the income they receive commensurate. They affect the revenue against discipline employees in complying with the values that have been applied by the company Indomaret. Employees strongly adhere to the rules applied by the company Indomaret, the values applied by Indomaret always be a benchmark for employees. Honesty employees are very in demand in the company so that all the work Indomaret Indomaret always be honest and are also responsible with specialization work they have lived. Concordance between fellow co-workers are also set in Indomaret values thus enjoined all employees work together always get along well among fellow employees. The relationship between employees and the leadership is very limited because leaders tend to have an authoritarian type of leadership so that all the wishes or commands that have been instructed to be done by employees of this case which resulted in restrictions between employees and leadership.Keywords: pattern, rate, rate of compliance.